(untitled) (Research, Society and Development, 2021)
The vulnerability shown by the pandemic caused by SARS-CoV-2, sparked a concern in the world population in establishing emergency containment measures. Although, so far, few studies have established sanitary sewage as a way of contamination by SARS-CoV-2, in Brazil the instability of wastewater disposal has established a warning about the inability of public systems to provide the implementation of collection and adequate treatment domestic effluents. This article presents evidence in national and international electronic scientific databases that corroborate a plurality of emerging technologies for the disinfection of applicable, efficient and safe wastewater for the disinfection of effluents in their treatment stages, preventing the discharge of potentially contaminated waste into the environment. Collaborating with disease mitigation and the necessary remodeling of effluent disinfection processes, considering the resources and the Brazilian reality.